Encampment policy and public perception: a cross-country analysis of host community responses to Rohingya refugees - Minakshi Keeni; Nina Takashino (Comparative Migration Studies)
Abstract This study examines the influence of encampment policies on host community perceptions towards Rohingya refugees in Bangladesh and Nepal, with an emphasis on how these perceptions shape the future of the refugees. Bangladesh, which has implemented an encampment policy, contrasts with Nepal, where no such policy exists. The research employs ordinary least squares (OLS) regression analysis to evaluate host community attitudes towards government policies, citizenship for newborns, and access to essential services like healthcare, jobs, education, and social security. The findings reveal that in Bangladesh, wealthier community members perceive less economic competition from refugees, particularly in job markets, due to the restrictions imposed by the encampment policy. However, social media in Bangladesh exacerbates negative perceptions, particularly concerning citizenship for Rohingya newborns, potentially hindering social cohesion. In Nepal, the absence of an encampment policy correlates with more negative perceptions among younger and economically vulnerable groups, who view refugees as competitors for limited resources. The study concludes that while encampment policies may mitigate immediate economic tensions, they risk deepening social divisions. Conversely, the lack of such policies in Nepal may lead to heightened resource competition and social tension. The research highlights the need for adaptive policy strategies that balance economic integration with social cohesion, ensuring sustainable refugee-host relations in both countries.